Analysis of Affine and Hill Cipher Method using Audio Steganography - Garg, Yashika (My University, 2017)
As the internet growing day by day secure transmission of data is very crucial. Steganography and Cryptography together helps us to provide data confidentiality and helps to protect the data from day by day attacks. So, the communication must be secretive as well as secure. In the proposed work, a comparative analysis of Affine and Hill Cipher method for Audio steganography using LSB (Least Significant method). Affine and Hill cipher are compared to each other on the basis of various factors such as Time Taken to embed the information, Frequency representation, PSNR, MSE etc.
Keywords: Audio Steganography; LSB (Least Significant Bit); PSNR-Peak signal to noise ratio; MSE-Mean Square error